Diseases of field crops diagnosis and management. Volume 1, Cereals, small millets, and fiber crops - Srivastava, J. N.; Singh, A. K. (Palm Bay, Fla. : Apple Academic Press, 2020)
Plant diseases cause yield loss in crop production, poor quality of produce, and great economic losses as well. Knowledge of the perpetuation and spread of the pathogens and various factors affecting disease development is an important need. Disease diagnosis is the prime requirement for determining preventive or curative measures for effective disease management. This new 2-volume set, Diseases of Field Crops, helps to fill the need for research on plant diseases, their effects, how they spread, and effective management measures to mitigate their harmful consequences. The volumes in this set showcase recent advances in molecular plant pathology and discuss appropriate diagnostic techniques for identification of causal agents and diseases, providing the information necessary to establish management strategies. The chapters in these two volumes include detailed description of symptoms, causal organisms, disease cycles, epidemiology, and management techniques of economically important diseases. The volumes explore existing strategies and offer new methods that can be used in an integrated manner and with a comprehensive approach for the management of major diseases of the field crops. Also taken into consideration is the impact of global climate change on the spread and severity of plant diseases. This volume focuses on a selection of cereal crops or grains for fodder and human food and the diseases that affect them. The crops include rice, maize, wheat, millet, sorghum, jute, and more. Volume 2 covers pulses, oil seeds, narcotics, and sugar crops.
Volume 1: Cereals, Small Millets, and Fiber Crops1. Present Scenario of Diseases in Rice (Oryza sativa L.) and Their ManagementS. Krishnam Raju et al.2. Disease Spectrum in Wheat and Barley under Different Agro-Ecological Conditions in India and Management StrategiesD. P. Singh, Sudheer Kumar, and Prem Lal Kashyap3. Ug99: Wheat Stem Rust Race: Exploring the WorldSudha Nandni, Devanshu Dev, and K. P. Singh4. Current Status of Bajra/Pearl Millet Diseases and their ManagementRanganathswamy Math, Kottramma C. Addangadi, and Durga Prasad Awasthi5. Diseases of Maize Crops and Their Integrated ManagementA. K. Singh et al.6. Brown Stripe Downy Mildew of Maize and Its Integrated ManagementAshwani K Basandrai and Daisy Basandrai7. Major Diseases of Sorghum and Their ManagementYogendra Singh, Divya Sharma, and Bhupendra Singh Kharayat8. Problem of Common Leaf Blight (Exserohilum turcicum (Pass.) Leonard & Suggs) in Sorghum and Their ManagementR. N. Bunker9. Banyard Millet/Japanese Millet or Sawan (Echinochloa frumentacea L.) Diseases and Their Management StrategiesBijendra Singh and J. N. Srivastava10. Common Millet or Proso Millet or Cheena Millet or French Millet (Panicum miliaceum L.) Diseases and Their Management StrategiesBijendra Singh and J. N. Srivastava11. Finger Millet or Ragi (Eleusine xoracana Gaertn.) Diseases and Their Management StrategiesBijendra Singh and J. N. Srivastava12. Foxtail Millet or Italian Millet or Halian Millet or Moha Millet or Kakun (Staria italika L.) Diseases and Their Management StrategiesBijendra Singh and J. N. Srivastava13. Kodo Millet or Kodo (Paspalum scorbiculatum L.) Diseases and Their Management StrategiesBijendra Singh and J. N. Srivastava14. Little Millet or Gundali or Goudli or Gondola (Panicum miliare L.) Diseases and Their Management StrategiesBijendra Singh and J. N. Srivastava15. Present Scenario of Diseases in Cotton and Their ManagementNiranjan Chinara and Kailash Behari Mohapatra16. Disease Spectrum in Jute and Their ManagementRajib Kumar De17. Present Scenario of Diseases of Jute and Their Integrated ManagementKunal Pratap Singh and J. N. Srivastava18. Nematode Diseases of Cereal Crops and Their ManagementVirendra Kumar Singh, Vivek Singh, and Deo Kumar
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Plant diseases -- Molecular aspects; Phytopathogenic microorganisms -- Control